Triacylglycerols are a Rich Source of Polyunsaturated Fatty Acids in Red King Crab Juveniles (Paralithodes camtschaticus) - Sikorskaya, Tatyana V. (Current Nutrition & Food Science, 2023)
In the Sea of Japan and the Okhotsk Sea, the red king crab Paralithodes camtschaticus is the major commercial species of the crab. The crab is a rich source of polyunsaturated fatty acids (PUFAs). The composition of triacylglycerol (TG) molecular species in freshly collected juveniles of P. camtschaticus has been determined for the first time. By supercritical fluid chromatography with mass-spectrometry, 45 molecular species of TG were identified. Most of the molecular species contained docosahexaenoic acid (DHA; 22:6n-3), eicosapentaenoic acid (EPA; 20:5n-3), arachidonic acid (AA, 20:4n-6), and monounsaturated fatty acid 18:1. Thus, DHA, EPA, and AA received from the diet are used to build phospholipids (PL) and also stored in TG in P. camtschaticus juveniles. Therefore, the crab is a rich source of PUFAs, which are concentrated both in structural PL and in reserve TG.
Keywords: supercritical fluid chromatography